Penerapan Model Pembelajaran Langsung dengan Menggunakan Metode Praktek terhadap Peningkatan Hasil Belajar Service Bawah Bolavoli pada Siswa Kelas X-3 SMAN 1 Pademawu - Hermanto, Mohammad; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study is a classroom action research aimed at improving the learning outcomes of volleyball underhand serve basic techniques in class X-3 students at SMAN 1 Pademawu through the implementation of a direct instruction model with a practical method. The research subjects were 34 students of class X-3. Data were collected through practical tests, as well as cognitive and affective observations. The results of the initial study (pretest) showed a very low learning mastery, with only 17.64% of students achieving the Minimum Completeness Criteria (KKM) of 65%. After the intervention was implemented, a significant improvement occurred in two cycles. In Cycle I, the percentage of learning mastery increased to 41.17%. Although there was an increase in the cognitive, psychomotor, and affective aspects, these results had not yet met the classical KKM, so the research was continued to Cycle II. In Cycle II, method improvements were made with more detailed instructions and stronger motivation. As a result, the percentage of mastery jumped to 76.47%, exceeding the set target. This indicates that the application of the direct instruction model with a practical method is significantly effective in improving student learning outcomes.